Research in phytochemical composition and hypoglycemic activity screening of the dry extracts from bearberry leaves - Chaika, Natalia; Mazen, Matar; Koshovyi, Oleh; Kravchenko, Ganna; Goryacha, Olga; Kireyev, Igor; Kovalenko, Sergiy; Darmograi, Roman (ScienceRise: Pharmaceutical Science, 2021)
Diabetes mellitus is a global medical and social issue. In the developed countries of the world, from 5 to 12% of the population are diagnosed with diabetes mellitus and, according to WHO prognosis, the level of this disease may increase to 30-35%. Type 2 diabetes is a disease that progresses over time, but the rational and systematic use of hypoglycemic synthetic drugs and phytopreparations can significantly delay the onset of insulin therapy. A promising source of BAS with a hypoglycemic effect is the raw material of plants of the Heather family, namely, bearberry leaves. However, on the Ukrainian market there are no domestic galenic and novo-galenic preparations based on biologically active substances of this raw material, which indicates the prospects for the development of new drugs, including those with hypoglycemic action. The aim. The aim of the study was to study the phytochemical composition and to carry out a screening of the hypoglycemic activity of dry extracts from bearberry leaves modified with various amino acids to identify promising substances with hypoglycemic action. Materials and methods. The objects of the study were 11 dry extracts from bearberry leaves, 10 of which were modified with various amino acids. The study of the phenolic compounds of the extracts was carried out by TLC, HPLC, and spectrophotometry. To assess the hypoglycemic activity of the extracts, two experiments were carried out - primary screening and oral glucose tolerance test. Results. Using TLC and HPLC, in the extracts obtained arbutin, gallic acid, 5 flavonoids were identified, among which hyperoside was dominant, 4 hydroxycinnamic acids, among which chlorogenic and caffeic acids were dominant, and their content was established. In the extracts obtained, main groups of phenolic compounds were quantified using a spectrophotometric method. Dry extracts from bearberry leaves, modified with cysteine, arginine and glutamic acid, showed the strongest hypoglycemic activity. Conclusions. The chemical composition of phenolic compounds and the hypoglycemic activity of dry extracts from bearberry leaves modified with 10 different amino acids were determined. The most promising substances turned out to be extracts modified with cysteine, arginine and glutamic acid; therefore, they are promising agents for the development of new drugs.